An integrated process for planning, delivery, and stewardship of urban nature-based solutions: the Connecting Nature Framework - Collier, Marcus (My University, 2023)
Mainstreaming nature-based solutions in cities has grown in scale and magnitude in recent times but is still considered to be the main challenge for transitioning our cities and their communities to be more climate resilient and liveable: environmentally, economically, and socially. Furthermore, taking nature-based solutions to the next level, and scaling them out to all urban contexts to achieve a greater impact, is proving to be slow and often conflicts with other transitioning initiatives such as energy generation, mobility and transport initiatives, and infilling to combat sprawl. So, the task is neither easy nor straightforward; there are many barriers to this novel transition, especially when it comes to collaborative approaches to implementing nature-based solutions with diverse urban communities and within city authorities themselves. This paper reports on a new process that is systematically co-produced and captured as a framework for planning nature-based solutions that emerged during the Connecting Nature project. The Connecting Nature Framework is a three-stage, iterative process that involves seven key activity areas for mainstreaming nature-based solutions: technical solutions, governance, financing and business models, nature-based enterprises, co-production, reflexive monitoring, and impact assessment. The tested and applied framework is designed to address and overcome barriers to the implementation of nature-based solutions in cities via a co-created, iterative, and reflective approach. The planning process guided by the proposed framework has already yielded promising results with some of the cities of the project, though further usage and its adoption by other cities is needed to explore its potential in different contexts especially in the Global South. The paper concludes with suggestions on how this may be realised.
Keywords: Nature-based solutions; Co-production; Connecting nature framework; 360 planning; Silos; Inclusive Society; International Development; International Integration; Smart & Sustainable Planet; CITIES; Co-production and co-creation; Connecting Nature; Connecting Nature Enterprise Platform; Connecting Nature Framework; E3; Fast-follower City; Front-runner City; LIveable Cities; NATURE-BASED SOLUTIONS; Nature Based Livelihood Communities; Nature-based enterprise; co-creation; co-production; eco-cities; Community; Development; Environment and housing; Policy; Social exclusion; Social participation